Research Trends in the field of English Language Teaching Methodology at Saudi Universities: An Analytical Study for selected MA Theses and Ph.D. Dissertations. - AlHarbi, Abdullah (DIRASAT: EDUCATIONAL SCIENCES, 2017)
In the last two decades, Saudi universities began to present post-graduate programs in the field of teaching English methodology. Many MA and PhD studies were done in TEFL field that required analyzing or examining those studies to determine their trends in order to guide future studies towards the effectiveness of the scientific studies in developing English language in Saudi Arabia.The current study analyzed 82 M.A and PhD research trends in the field of TEFL in the areas of :• Research topic..• Research methodology.• Research tools.• Research targets• Research targeted educational stage. The findings of the study revealed that:1. Teaching methodology was the first topic that addressed by the target studies (53.7%) ,second topic was Evaluation (15.9%) and the third was Using technology in teaching English language (14.6%). 2. There is less repetition in the first topic titles than the second and third topics.3. The quasi-experimental studies (55%) are more than the descriptive studies (44%) in the total of target studies.4. Test is the most usable tool (46%) in the target researches. The second tool was questionnaire (26%).5. Secondary stage is most stage targeted by M.A. and PhD. studies (40%), the second stage is intermediate = 34%.6. The male students (40%) were the most targeted as population for MA and PhD studies. Then, female students (20.5%), Male teachers (19.5%), female teachers (9%) and content (11%).The study recommended to:1. Avoid the repeated titles in the future studies.2. Use more research methods in the future studies especially qualitative ones. 3. Use more types of research tools in the future studies.4. Do further studies in the stages that have less studies as primary stage and university stage.5. Do further studies in the field of TEFL targeted female students and teachers. 6. Open more PhD programs in the field of teaching English language methodology